The Post-Imperial Politics of Security and Depoliticisation: Comparing Discourses and Practices of Ordering Across Central Asia. Issue 2 (7th February 2022) - Bonacker, Thorsten; Lottholz, Philipp
Abstract: In this essay, we build on earlier discussions on the insufficiency of labels such as 'post-Soviet' and 'postcolonial' for Central Asian regimes and propose a consideration of their particular post-imperial character. We illustrate the usefulness of this lens through an analysis of security and violent conflicts in Central Asia and how governments interpret and present these conflicts. Our discussion draws systematically on existing research on relevant processes in Kazakhstan, Kyrgyzstan, Uzbekistan and Tajikistan, allowing us to identify key themes of a post-imperial politics of security and their implications in a comparative perspective.